Mapping the field: a systematic review of non-professional interpreting and translation in Italy. - Ceccoli, Federica (Estudios de Traducción, 2026)
This paper presents a systematic review of the current research literature on non-professional interpreting and translation (NPIT) in public services in the Italian context, a critical area of research given the increasing demand for effective communication in diverse communities. Non-professional interpreting and translation, often carried out by adult and child bilingual individuals without formal training, has gained increasing attention due to its relevance in multicultural and multilingual settings such as health, legal and educational services, particularly in response to Italy’s growing immigrant population. Non-professional interpreters and translators, often community members or bilingual staff, play a vital role in facilitating access to essential services, yet their work is frequently underrecognized and under-researched. This review synthesizes existing literature from the last two decades, highlighting the methodologies, contexts, and outcomes of non-professional interpreting practices across various public service sectors, including healthcare and education. The findings offer insights into the role of NPIT in Italy, highlighting its relevance for public policy and social inclusion strategies. By identifying gaps in current research and practice, this review aims to inform future studies and improve the efficacy of interpreting and translation services in public contexts, ultimately fostering better communication and equity for non-native speakers in society.